Awareness of Millets and their Health Benefits among Patients with Diabetes - Sure Sai Sravani; Vanishree Shriraam (Journal of Diabetology)
Background: The glycemic index (GI) of a food can vary from low to high depending on several factors such as the form of food, ingredient, and method of preparation. In general, rice and wheat are known to have higher GI, making unpolished and unrefined millet a better choice for managing diabetes. Objectives: This study aimed to assess the awareness, type, and form of millet consumed, reasons for consuming and not consuming millet, duration and frequency of millet consumption, and source of information on millet, which was followed by assessment of the increase in knowledge after health education among people with diabetes (PWD). Materials and Methods: This is a hospital-based cross-sectional study conducted among PWD in the Endocrine Outpatient Department (OPD) at a teaching hospital. A questionnaire for assessing background information, knowledge, and consumption patterns of millets was prepared, pre-tested, and administered to the PWD. Health education on millet was given, and the knowledge and attitude sections of the questionnaire were re-administered to the study participants by the one-on-one method. Data were collected using Google Forms, and SPSS 16.0 was used for data analysis. Results: In this study, a total of 146 PWD participated, including 98 females and 48 males. The mean age of the participants was 52.9 years (SD-13.1). It was found that 90.4% and 52.0% of patients were aware of commonly consumed millets (ragi, bajra, and foxtail millet) and less commonly consumed millets (kodo millet, barnyard millet, and little millet). Among participants, 76% consumed millets at least two to three times per week, and 45.2% of patients were aware of the health benefits of millets and their role in controlling diabetes. Among consumers, 39% have started taking millets in the past 1 year. In the last 3 months, only 47.9% of doctors/nutritionists/nurses had encouraged and advised their patients on millet consumption and its importance. There was a significant increase in knowledge after health education (P < 0.001*). Conclusion: Healthcare providers should increase awareness and educate PWD on how millet consumption in proper forms and frequency can help in the prevention and management of diabetes.